Caspase‐1‐dependent mechanism mediating the harmful impacts of the quorum‐sensing molecule N‐(3‐oxo‐dodecanoyl)‐l‐homoserine lactone on the intestinal cells. Issue 4 (23rd November 2018) - Tao, Shiyu; Sun, Qinwei; Cai, Liuping; Geng, Yali; Hua, Canfeng; Ni, Yingdong; Zhao, Ruqian
Abstract: N‐(3‐oxododecanoyl)‐l ‐homoserine lactone (3‐oxo‐C12‐HSL), a quorum‐sensing (QS) molecule produced by Gram‐negative bacteria in the gastrointestinal tract, adversly impacts host cells. Our previous study demonstrated that 3‐oxo‐C12‐HSL induced a decrease in cell viability via cell apoptosis and eventually disrupted mucin synthesis from LS174T goblet cells. However, the molecular mechanism underlying cell apoptosis and whether pyroptosis was involved in this process are still unknown. In this study, we emphasized on the caspases signal pathway and sterile inflammation to reveal the harmful effects of 3‐oxo‐C12‐HSL on LS174T goblet cells. Our data showed that 3‐oxo‐C12‐HSL is a major inducer of oxidative stress indicated by a high level of intracellular reactive oxygen species (ROS). However, TQ416, an inhibitor of paraoxonase 2, can effectively block oxidative stress. A higher ROS level is the trigger for activating the caspase‐1 and 3 cascade signal pathways. Blockade of ROS synthesis and caspase‐1 and 3 cascades can obviously rescue the viability of LS174T cells after 3‐oxo‐C12‐HSL treatment. We also found that paralleled with a higher level of ROS and caspases activation, an abnormal expression of proinflammatory cytokines was induced by 3‐oxo‐C12‐HSL treatment; however, the blockage of TLRs‐NF‐κB pathway cannot restore cell viability and secretary function. These data collectively indicate that 3‐oxo‐C12‐HSL exposure induces damages to cell viability and secretary function of LS174T goblet cells, which is mediated by oxidative stress, cell apoptosis, and sterile inflammation. Overall, the data in this study will provide a better understanding of the harmful impacts of some QS molecules on host cells and their underlying mechanism. Abstract : 3‐Oxo‐C12‐HSL induces oxidative stress and caspase‐1‐caspase‐3 activation in LS174T cells. Inhibition of PON2 eliminates 3‐oxo‐C12‐HSL induced oxidative stress and cell death. N‐acetyl‐l‐cysteine reversed 3‐oxo‐C12‐HSL induces caspase‐1 and caspase‐3 activation. Caspase‐1 and caspase‐3 inhibitor rescue mucin synthesis disorder induced by 3‐oxo‐C12‐HSL.